Sharpening of the Explicit Lower Bounds for the Order of Elements in Finite Field Extensions Based on Cyclotomic Polynomials - Popovych, R. B. (Ukrains’kyi Matematychnyi Zhurnal, 2014)
We explicitly construct elements of high multiplicative order in any extensions of finite fields based on cyclotomic polynomials.